SOSIALISASI SISTEM REKRUTMEN GURU HONORER BERBASIS KOMPETENSI UNGGUL DAN NILAI KEALKHAIRAATAN PADA YAYASAN ALKHAIRAAT KOTA GORONTALO - Sofyan Alhadar Sofyan (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
The quality of teachers is a critical determinant of learning outcomes, yet many educational foundations in Indonesia still lack a standardized, competency-based recruitment system for honorary teachers. This community service activity aimed to enhance the understanding of foundation administrators, madrasah heads, and teachers regarding a recruitment system that integrates core teaching competencies with the specific values of Kealkhairaatan at the Alkhairaat Foundation, Gorontalo City. The participatory socialization method was employed, involving 16 participants through interactive lectures, group discussions, case simulations, pre-test and post-test assessments, and satisfaction questionnaires. The activity was conducted in four stages: preparation, implementation, evaluation, and follow-up. Results showed a significant increase in participant understanding, with the average post-test score rising from 58.4 to 82.6 (a 41.4% improvement). The highest gain was observed in understanding the integration of Kealkhairaatan values in the selection process (from 40% to 85%). Participant satisfaction averaged 3.7 out of 4.0. A concrete policy recommendation for an integrated recruitment guideline was produced. This activity demonstrates that a structured, participatory socialization approach effectively builds capacity for more professional and value-based teacher recruitment in Islamic educational institutions.